Therapeutic advancement of chronic lymphocytic leukemia - Lu, Kang (BioMed Central, 2012)
Despite the combinations of chemotherapy with monoclonal antibodies have further improved response rates, chronic lymphocytic leukemia (CLL) remains an incurable disease with an extremely variable course. This article reviews the ongoing clinical advances in the treatment of CLL in both previously untreated and relapsed disease and focuses on the benefit of different therapeutic strategies, the most effective therapy combinations and the potential activity of novel agents. Novel agents and combination therapies have been investigated by several studies in both the upfront and relapsed setting, particularly for patients with 17p deletion, TP53 mutation and fludarabine-refractory CLL. While these agents and combination therapies have improved initial response rates, ongoing studies are continued to determine and improve the efficacy and safety. Despite advancements in the treatment of CLL have led to high response rates, allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains the only curative option and reduced-intensity conditioning (RIC) allo-HSCT must be strongly considered whenever feasible. As such, ongoing studies of these agents and other novel approaches in clinical development are needed to expand and improve treatment options for CLL patients.